Perioperative evaluation of anatomy of urinary bladder and urethra in ultrasound examination of female patients operated due to urinary stress incontinence - Brzeziński, Marek; Żurawik-Pietrzak, Anna; Ostrowski, Dariusz; Żurawik, Tadeusz; Wielgoś, Mirosław (Menopause Review/Przegląd Menopauzalny, 2013)
Aim of the study: The aim of the thesis was to analyse selected ultrasound parameters concerning anatomy of the lower part of the urinary tract in female patients operated due to stress incontinence. Material and methods: The study was prospective and included 43 patients, who had the suburethral tape implemented during the procedure. Perineal ultrasound examination in the supine position was performed before and 3-6 days after the procedure. Measurements were performed at rest and during the Valsalva test. The following parameters were evaluated: posterior urethro-vesical angle – β, urethral angle curve, height and distance of urinary neck from pubic symphysis – Dy and Dx, angle alteration at the Valsalva test – Δβ, urinary neck mobility at the Valsalva test and other. Results : The average value of posterior urethro-vesical angle β at rest did not change after the surgery, but in the case of the Valsalva test it decreased from 150.6 ±17.9 before to 127.5 ±15.1 after surgery. We also observed a difference in angle alteration with the Valsalva test from 32.2 ±19.7 before to 5.4 ±11.3 after the procedure. At the Valsalva test after the operation the urinary bladder neck was closer to pubic symphysis, while urinary bladder neck mobility at the Valsalva test, after the procedure decreased significantly. Conclusions : Sling surgeries influence numerous mechanisms responsible for urinary continence: they decrease posterior urethro-vesical angle under pressure, they approach and lift urethra to pubic symphysis under pressure and decrease urethral mobility.